Employing an Innovative Stepwise Current Density Regime and Modified Electrolyte to Enhance Surface Performance of Anodized 6061 Aluminum - Soroush Asgharian; Reza Khadem; Meisam Nouri; Hassan Elmkhah; Ahmad Ahmadi Daryakenari (Engineering Reports, 2025)
ABSTRACT With the goal of improving both tribological and corrosion resistance, this study investigates if a novel stepwise current density regime in conjunction with a modified electrolyte composition during the hard anodizing process of 6061‐T6 aluminum could benefit wear and corrosion resistance. Although the effects of various electrolyte additions and current density techniques on anodization have been studied in the past, little is known about how they interact to affect the coating characteristics. By utilizing a galvanostatic regime to optimize the anodizing process in an electrolyte based on sulfuric acid and adding citric and oxalic acids, our work bridges this gap. The anodized coatings were evaluated through wetting angle measurements, hardness assessments, roughness analysis, scanning electron microscopy (SEM), and grazing incidence X‐ray diffraction (GIXRD). Corrosion performance was analyzed using electrochemical impedance spectroscopy (EIS), while tribological parameters were determined through solid particle erosion and pin‐on‐disk wear testing. The results demonstrated a substantial improvement in coating performance due to the combined effects of the modified electrolyte and stepwise current density method. Specifically, the optimized process led to a 68% increase in coating thickness, a 313% increase in corrosion resistance, and improvements of 74% and 52% in erosion and wear resistance, respectively, along with a 45% increase in hardness. Furthermore, a dense uniform layer with a graded hardness profile from the surface to the interface was achieved, while GIXRD analysis confirmed the formation of an amorphous structure with hard ion carboxylates. The results offer a scalable and practical method to improve the surface performance of anodized aluminum alloys by revealing a fresh understanding of the synergistic effects of current density modulation and electrolyte modification.